Self-acupressure for patients with breast cancer experiencing aromatase inhibitor-associated musculoskeletal symptoms: Protocol for the AcuAIM randomized pilot trial - N. Lynn Henry; Kelley M. Kidwell; Stephanie Kozar; Sara Snyder; Suzanna M. Zick (PLoS ONE, 2025)
Background Aromatase inhibitors (AI) reduce hormone receptor-positive breast cancer recurrence risk by about 50%. However, half of AI-treated postmenopausal women report new or worsened musculoskeletal symptoms (AIMSS), and 20% discontinue therapy prematurely. Acupuncture is effective for reducing symptoms, but many women are not able to access acupuncture therapy. We hypothesize that self-administered acupressure will reduce AIMSS. Materials and methods Postmenopausal women who have been receiving treatment with an AI for more than 3 weeks but less than 2 years, and who report new or worsened joint pain or myalgias since starting AI therapy with worst pain of at least 4 out of 10 on a numerical rating scale, are eligible. Fifty participants will be enrolled and randomized 1:1 to treatment with true or sham acupressure for 12 weeks. Participants will self-apply pressure for 3 minutes to each of the 9 acupoints daily. All participants will complete a pain assessment weekly, and a battery of symptom questionnaires every 6 weeks. Optional stool samples will be collected after 0 and 12 weeks of acupressure to examine changes in the gut microbiome. The primary endpoint is change in worst pain on the Brief Pain Inventory-Short Form with 12 weeks of the acupressure intervention, evaluated with generalized estimating equations. Conclusion Determination that self-administered acupressure reduces AIMSS in this randomized phase 2 pilot trial will lead to a larger randomized phase 3 clinical trial to confirm the efficacy of self-acupressure. Reduction of AI-related arthralgias may improve persistence with breast cancer therapy, breast cancer outcomes, and quality of life for AI-treated patients. Trial registration Clinicaltrials.gov NCT06228768.